MINERALISASI BIJIH DAN KARAKTERISTIK LARUTAN HIDROTERMAL PADA ENDAPAN EPITERMAL LOGAM DASAR DI BUONG BARU, KECAMATAN SESAYAP HILIR, KABUPATEN TANA TIDUNG, PROVINSI KALIMANTAN UTARA, INDONESIA - , ARFIAN FIRMANSYAH ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Research area has a potential base-metal deposit. This area is located at Buong Baru district western of Tarakan Island. Some researched suggest that this region has potential for lead and zinc deposit. Another research of geological survey mentions that there are some mineral alteration indication which may be related mineralization. Therefore, exploration in this area may become important. One of this exploration subject is to understanding the genetic of the deposit which needed for understanding further examination. This research is aimed to understand ore mineralization and hydrothermal fluid characteristics of epithermal deposit in research area. For this purpose, geological study analysis, ore mineralogical observation, and fluid inclusion study is aimed for collecting data. Further, compilation of this examination used to build genetic model of this area, especially for fluid evolution. Interpretation of those data indicates that hydrothermal fluid consist of two phase hypogen deposition. On early phase, deposition take place at temperature of 265 â 300 o C which lead to deposition of galena, chalcopyrite, sphalerite and pyrite. On last phase, deposition of pyrite, sphalerite, covellite, and gold occur at 240 â 265 o C. Hydrothermal fluid also indicates a mixing condition which shown by general trend of homogenization temperature-salinity graphic plot. This mixing is interpreted as mixing both magmatic fluids with meteoric water. In the development of mixing phase, meteoric water become dominated which indicated by low salinity of trapped fluids. This fluid mixing condition may act as the key of this deposit which is circulated in epithermal intermediate- sulfidation system